2011
DOI: 10.1002/ijc.25492
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic significance of placental growth factor in hepatocellular carcinoma and peritumoral liver tissue

Abstract: Vascular endothelial growth factor‐targeted therapy is a promising treatment for hepatocellular carcinoma (HCC), but its clinical benefit is often accompanied by acquired resistance. In animal studies, antiplacental growth factor therapy is effective with less resistance. The role of placental growth factor (PlGF) in the progression of HCC is not clear. In our study, we used immunohistochemistry in tissue microarrays to investigate PlGF expression in tumor and peritumoral liver tissues from 105 patients with H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…On the other hand, it has been reported that in the peritumor area of human hepatocellular carcinoma, the level of PlGF was significantly increased and correlated with augmented levels of HIF-1α. 55 Finally, since PlGF also positively modulates HIF-1α expression in ECs, 56 a positive loop may be established to maintain high levels of PlGF expression when required.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been reported that in the peritumor area of human hepatocellular carcinoma, the level of PlGF was significantly increased and correlated with augmented levels of HIF-1α. 55 Finally, since PlGF also positively modulates HIF-1α expression in ECs, 56 a positive loop may be established to maintain high levels of PlGF expression when required.…”
Section: Discussionmentioning
confidence: 99%
“…PlGF plays a role in angiogenesis only under pathological conditions, such as in hepatocellular carcinoma in which they have investigated the role of the PlGF/Flt-1 pathway [31,32]. There is a synergistic co-operation between PlGF and VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…The identification and regulation of factors responsible for these angiogenic processes are areas of active investigation, as these pathways could provide valuable targets for therapeutic intervention, especially in HCC in which the multikinase inhibitor sorafenib (Nexavar) is currently the standard of care for advanced HCC patients [3][4][5]. The vascular endothelial growth factor (VEGF) has gathered extensive attention for its role in mediating tumour angiogenesis [6][7][8][9], but recently interest in the placental growth factor (PlGF) [10][11][12][13][14] has grown. PlGF is a VEGF homologue, which is only involved in pathologic angiogenesis; therefore, its inhibition does not induce side-effects [14,15].…”
mentioning
confidence: 99%